Does reputation matter? Evidence from share repurchases - Ota, Koji; Kawase, Hironori; Lau, David (Journal of Corporate Finance, 2019)
This paper examines whether the stock market considers the firm's reputation established through a history of management earnings forecasting when it evaluates open market repurchase announcements. We refer to this established reputation as the firm's “forecast reputation”. We find that while the stock market considers the firm's “repurchase reputation” (proxied by prior repurchase completion rates), it also considers the firm's forecast reputation established from the accuracy of prior management earnings forecasting, suggesting a spillover effect of forecast reputation. Further, interaction test between the two reputation variables reveals that the market reacts more to the firm's forecast reputation when its repurchase reputation is low. Additional analyses suggest that when a firm announces a share repurchase program for the first time (i.e., when there is no repurchase reputation), investors turn to the forecast reputation within the firm as an alternative source of reputation, on which the credibility of repurchase announcements is assessed. Overall, our study provides evidence that firms establish a reputation in the market through multiple sources of announcements.